The ageing of the labour market and its impact on the balance of the pension system in Algeria - Adda, Leila; Khadra, Rachedi (The International tax journal, 2025)
This research aims to study the ageing of the labour market and its impact on the balance of the pension system. In Algeria, demographic changes have resulted in a phenomenon of an ageing workforce, which has impacted the dynamism of the labour market. At the same time, this phenomenon has had direct consequences for pension financing. The National Retirement Fund (CNR), which manages pensions, has recorded net deficits since 2013, shifting from a surplus of -110,540 million in 2012 to a deficit of 85,762 million in 2013. In order to address this deficit, it will be necessary to raise the retirement age, increase the number of working years, raise contribution rates for workers and employers, or diversify funding sources.